Servicio al cliente de la Distribuidora de Plástico y Calzado Aguilar de la ciudad de Babahoyo en el periodo 2021. - Chang Mora, Flavio Ricardo (2022)
This case study focuses on the analysis of the customer service process of Distribuidora de Plástico y Calzado Aguilar in the city of Babahoyo in the period 2021. The importance of approaching this project lies in evidencing the importance of a correct customer service, since it contributes to the loyalty of users and why not, to acquire new consumers. The research methodology implemented was of mixed qualitative and quantitative character; as part of the instruments used is the observation sheet, interview and survey which was directed to a group of customers of the Distributor. Finally, with the culmination of the research work, it was established how the customer service process affects the productivity level of the Distribuidora de Plástico y Calzado Aguilar in the city of Babahoyo. Simultaneously, conclusions were obtained that offer a broader picture of the situation within the company.